2006
DOI: 10.1111/j.1365-2486.2006.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Wood properties of two silver birch clones exposed to elevated CO2 and O3

Abstract: Effects of elevated carbon dioxide (CO 2 ) and ozone (O 3 ) on wood properties of two initially 7-year-old silver birch (Betula pendula Roth) clones were studied after a fumigation during three growing seasons. Forty trees, representing two fast-growing clones (4 and 80), were exposed in open-top chambers to the following treatments: outside control, chamber control, 2 Â ambient [CO 2 ], 2 Â ambient [O 3 ] and 2 Â ambientAfter the 3-year exposure, the trees were felled and wood properties were analyzed. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 53 publications
3
36
3
Order By: Relevance
“…Atkinson and Taylor (1996) showed that elevated [CO 2 ] increased vessel diameters in the ring-porous wood of Quercus robur seedlings. On the other hand, no obvious effect was found in diffuse-porous woods including that of Populus tremuloides (Kaakinen et al 2004) and Betula pendula (Kostiainen et al 2006), whereas the vessel lumen area increased significantly in seedlings of Quercus ilex under high [CO 2 ] (Gartner et al 2003).…”
Section: Introductionmentioning
confidence: 56%
“…Atkinson and Taylor (1996) showed that elevated [CO 2 ] increased vessel diameters in the ring-porous wood of Quercus robur seedlings. On the other hand, no obvious effect was found in diffuse-porous woods including that of Populus tremuloides (Kaakinen et al 2004) and Betula pendula (Kostiainen et al 2006), whereas the vessel lumen area increased significantly in seedlings of Quercus ilex under high [CO 2 ] (Gartner et al 2003).…”
Section: Introductionmentioning
confidence: 56%
“…The concentration of O 3 has been increasing rapidly because of the anthropogenic emissions of several O 3 -forming gases (Katri et al 2006). This increase is expected to continue unabated for the foreseeable future (Luis et al 1996).…”
mentioning
confidence: 99%
“…In the boreal forest, soil CO 2 fluxes to the atmosphere increase with increased temperature and atmospheric CO 2 concentration (Niinisto et al, 2004), although many uncertainties remain (Fang and Moncrieff, 2001;Ågren and Bosatta, 2002;Hyvönen et al, 2005). Climate change may induce a reallocation of carbon to foliage (Magnani et al, 2004;Lapenis et al, 2005) and lead to carbon losses (White et al, 2000;Kostiainen et al, 2006;Schaphoff et al, 2006). Climate change may alter the chemical composition and density of wood while impacts on wood anatomy remain uncertain (Roderick and Berry, 2001;Wilhelmsson et al, 2002;Kostiainen et al, 2006).…”
Section: Forestsmentioning
confidence: 99%
“…Climate change may induce a reallocation of carbon to foliage (Magnani et al, 2004;Lapenis et al, 2005) and lead to carbon losses (White et al, 2000;Kostiainen et al, 2006;Schaphoff et al, 2006). Climate change may alter the chemical composition and density of wood while impacts on wood anatomy remain uncertain (Roderick and Berry, 2001;Wilhelmsson et al, 2002;Kostiainen et al, 2006).…”
Section: Forestsmentioning
confidence: 99%